The Role Of Green Human Resource Management In Improv-ing Green Organizational Performance: A Qualitative Litera-ture Review - Patswawati, Patswawati; Pujiati, Herni (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study explores the crucial role of green Human Resource Management (HRM) in driving improved green organizational performance. Using a qualitative literature review method, this study analyzes published studies to identify effective green HRM practices and their impacts on dimensions of sustainable organizational performance, including environmental, economic, and social performance. The review results indicate that the integration of sustainability principles in HRM functions, such as recruitment, training, development, compensation, and performance management, significantly contributes to the achievement of green organizational goals. This study provides valuable insights for practitioners and academics to formulate more comprehensive green HRM strategies.